Analysis of Work Readiness of Automotive Engineering Students of SMKS Pembda Nias Regional School Reviewed in Terms of Hard and Soft Skills - Desman Telaumbanua; M. Giatman; Ambiyar; Dedy Irfan (Jurnal Penelitian Pendidikan IPA, 2025)
Hard skills and soft skills are two fundamental components that simultaneously form the construct of work readiness. In the context of automotive engineering, hard skills refer to the mastery of specific technical skills such as engine failure diagnosis, transmission system repair, Electronic Control Unit (ECU) calibration, and a deep understanding of the working principles of automotive components. This study aims to analyze in depth the work readiness of Automotive Engineering students at SMKS Pembda Nias in terms of the hard and soft skills they possess. This study is a quantitative study using a correlational method. The results of this study; Transmission system repair skills were the most dominant indicator with an achievement level of 82.8%, followed by understanding vehicle electronic systems (82.60%), computer diagnostic tool skills (82%), automotive technology handling (81%), and mastery of engine failure diagnosis (80.40%). This good level of mastery indicates that students have sufficient technical competence to work in the automotive field. Meanwhile, the level of achievement of students' soft skills was also in the good category with an achievement level of 82.5%. Work ethic and professionalism were the most dominant indicators with an achievement level of 83.50%, followed by teamwork skills (82.90%), effective communication skills (82.60%), time management skills (82.30%), and adaptability to change (81.40%).